Effect of a concurrent training session with different intensities in post-exercise blood pressure responses in normotensive adults - André Luiz F Medeiros; Manoela Vieira Sousa; Morgana Lunardi; Silas Nery Oliveira; Cintia de la Rocha Freitas (Desafio Singular, 2018)
Effect of a concurrent training session with different intensities in post-exercise blood pressure responses in normotensive adults. The purpose of this study was to analyze the effect of a concurrent training session (CT) with different intensities in post-exercise blood pressure responses in normotensive adults. Ten normotensive adult males participated in this study, they performed four experimental protocols: a) Strength Training (ST) at 50% of 1RM and aerobic training (AT) between 50-60% of the Working Heart Rate (WHR), b) ST at 50% of 1RM and AT between 80-90% of the WHR, c) ST at 85% of 1RM and AT between 50-60% of the WHR, d) ST at 85% of 1RM and AT between 80-90% of the WHR. Every protocol presented a decrease in the systolic blood pressure 1 minute after finishing the training session, however, only the protocol with the intensity of 50% 1RM and 80-90% WHR presented a significant hypotensive effect (p ≤ 0,05). None of the protocols presented a significant decrease in the diastolic blood pressure. We came to the conclusion that the hypotensive effect in the SBP can be observed when the CT is performed at the intensity of 50% of 1RM and of 80-90% of the WHR.